2021
DOI: 10.1016/j.pmedr.2021.101436
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk of harm from monthly cannabis use among US adolescents: National Survey on drug Use and Health, 2017

Abstract: There has been a steady increase in cannabis use among US adolescents over the past decade. Perceptions of risk, specifically the belief that cannabis use is not harmful, may contribute to this increased use. The purpose of this study was to evaluate parental, school, and peer influence as protective factors in perceiving there is risk of harm from monthly cannabis use. Using the 2017 National Survey on Drug Use and Health (NSDUH), the study outcome was self-reported perceived risk of harm from monthly cannabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…This latter finding is particularly alarming, as studies consistently cite a link between lower cannabis harm perceptions and greater likelihood of problematic cannabis use. 28 Finally, exposure to print marketing was negatively associated with positive attitudes about cannabis and lower perceptions harm. In our sample, multivariable regression models showed that print marketing exposure was most common among mid-life adults (ages 25-44), who may have less positive attitudes about cannabis use overall, and who also have lower rates of internet and social media use compared to young adults.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This latter finding is particularly alarming, as studies consistently cite a link between lower cannabis harm perceptions and greater likelihood of problematic cannabis use. 28 Finally, exposure to print marketing was negatively associated with positive attitudes about cannabis and lower perceptions harm. In our sample, multivariable regression models showed that print marketing exposure was most common among mid-life adults (ages 25-44), who may have less positive attitudes about cannabis use overall, and who also have lower rates of internet and social media use compared to young adults.…”
Section: Discussionmentioning
confidence: 97%
“…In regression models that simultaneously controlled for the potential overlap among all CME sources, those exposed to outdoor marketing and social media marketing reported more positive attitudes about cannabis use and were more likely to report past 30‐day cannabis use and lower cannabis harm perceptions. This latter finding is particularly alarming, as studies consistently cite a link between lower cannabis harm perceptions and greater likelihood of problematic cannabis use 28 . Finally, exposure to print marketing was negatively associated with positive attitudes about cannabis and lower perceptions harm.…”
Section: Discussionmentioning
confidence: 98%
“…Similar questions were posed to respondents regarding peer behaviors ("How do you think your close friends would feel about you smoking one or more packs of cigarettes a day?"). The parental disapproval variable (yes vs. no) and the peer disapproval variable (yes vs. no) were dichotomized from these survey questions as per previous research, 28 in which any degree of perceived disapproval (somewhat disapprove and strongly disapprove) was classified as "yes" and responding neither approve nor disapprove was categorized as "no." Missing responses (N ¼ 1,584, 2.9%) were excluded from analysis.…”
Section: Measure Of Perceived Parental and Peer Attitudesmentioning
confidence: 99%
“…High parental monitoring and negative peer attitudes toward cannabis use act as protective factors against cannabis use. In a study by Mariani et al, 67 those children who perceived that their peers disapproved of cannabis use, believed that cannabis use was risky, and that school was important were less likely to use. Active involvement in extracurricular activities was also protective.…”
Section: Cannabidiolmentioning
confidence: 99%